Designing the Space Archivists: A Metadata-Driven VR Game Concept for Children to Engage with Cultural Heritage - Alina Goldman; Rasa Bocyte; Elana B. Blinder; Arno Verhofstadt; Elizabeth Bonsignore; Pablo Cesar (Heritage)
Motivated to create a children’s VR game for the Netherlands Institute for Sound and Vision (NISV), this research asks how might we design an immersive game for children to meaningfully interact with media and metadata in cultural heritage contexts? First, during a ‘design salon,’ 13 data and heritage experts challenged children’s ability to interact with metadata. In response, we ran workshops with 19 children focused on understanding abstract media and data. We found that while (1) metadata has many challenges, (2) children understand abstract data when it is grounded in concrete experiences, are (3) motivated to interact with archival media through in immersive and collaborative contexts, and (4) are interested in exploring media diversity through categorisation games with high-level narrative goals. These findings inform our game concept and three core insights for designing immersive experiences for cultural heritage: Considering the Contextual Complexity of Data and Audience Needs, Connecting Data Abstractions to Embodied Narratives Through Categorisation Mechanics, and Supporting Abstract Meaning Making Using the Immersive Affordances of VR.